1, 2, 4‐Triazol‐5‐ylidenes versus Imidazol‐2‐ylidenes for the Stabilization of Phosphorus(I) Cations. Issue 22 (27th September 2016) - Elnajjar, Fawzia O.; Binder, Justin F.; Kosnik, Stephanie C.; Macdonald, Charles L. B.
Abstract : The synthesis and characterization of a series of 1, 4‐dialkyl‐1, 2, 4‐triazolium iodide and tetraphenylborate salts featuring methyl, ethyl, and isopropyl substituents and their use as precursors, in conjunction with triphosphenium reagents, to generate 1, 4‐dialkyl‐1, 2, 4‐triazol‐5‐ylidene‐stabilized phosphorus(I) ions is described. The use of tetraphenyl borate salts of both reagents produces the most pure products. The structural and spectroscopic features of the products are compared to those of analogous ions featuring 1, 3‐imidazol‐2‐ylidene ligands. Abstract :